(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Physiology of the traditional Ayurvedic diagnostic technique of Nadipariksha has always been a matter of controversy. This diagnostic skill is based on a fine tactile sensitivity of the physician to distinguish varied intensities of mechanical vibrations elicited by radial artery pulsation, normally perceived as Pulse Pattern Variability (PPV). Ancient exponents of Yoga and Ayurveda define Nadi as the channel of Prana which is known as the very basis of bio-energy dynamics of the body. To the modern physician Nadipariksha indicates an assessment of cardiac function which is an important aspect of vascular physiology. The above concept has been re-examined in this article, in the light of whole body bio-electrical activity pattern. The study suggests Nadi as the Energy Pulsating Pathway (EPP) encompassing cells Pulsating Bio-Electrical Response (PBER). The observed varying intensities of PPV in Nadipariksha are proposed to be due to collision of weak threshold PBER with the mechanical vibration of pulsating radial artery. The underlying mechanism of Nadipariksha has been proposed to be associated with energy dynamics of bio-electrical waveform activity at the cellular level. This approach points at its possible implications in developing a more objective diagnostic method in assessing psycho-physiological abnormalities of a patient without having to depend on the subjective diagnostic judgment of a physician. Further, this study hints at the possible experimental evidence towards a physiological evaluation of Nadipariksha through the measures of bio-impedance, bio-reactance and bio-phase angle.